2010
DOI: 10.1099/ijs.0.014506-0
|View full text |Cite
|
Sign up to set email alerts
|

Kocuria atrinae sp. nov., isolated from traditional Korean fermented seafood

Abstract: A novel actinobacterium, strain P30T , was isolated from jeotgal, a traditional Korean fermented seafood. Cells were aerobic, Gram-positive, non-motile and coccoid. Optimal growth occurred at 30-37 6C, at pH 8-9 and in the presence of 0-2 % (w/v) NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The major menaquinones detected for the strain FCS-11 T were MK-7(H 2 ) 26.3%, MK-8(H 2 ) 31.4% and MK-9(H 2 ) 42.1%. It was also observed that the strains K. atrinae P30 T and K. salsicia 104 T had menaquinones MK-7(H 2 ), MK-8(H 2 ), MK-9(H 2 ) and MK-7(H 2 ), MK-8(H 2 ) respectively, which are typical of the genus Kocuria (Stackebrandt et al 1995); in contrast Yun et al (2011) and Park et al (2010a) had incorrectly reported the presence of MK-7 as the predominant menaquinone in each of these strains. Based on the above observation Growth at/on:…”
Section: Chemotaxonomic Characterisationmentioning
confidence: 87%
See 1 more Smart Citation
“…The major menaquinones detected for the strain FCS-11 T were MK-7(H 2 ) 26.3%, MK-8(H 2 ) 31.4% and MK-9(H 2 ) 42.1%. It was also observed that the strains K. atrinae P30 T and K. salsicia 104 T had menaquinones MK-7(H 2 ), MK-8(H 2 ), MK-9(H 2 ) and MK-7(H 2 ), MK-8(H 2 ) respectively, which are typical of the genus Kocuria (Stackebrandt et al 1995); in contrast Yun et al (2011) and Park et al (2010a) had incorrectly reported the presence of MK-7 as the predominant menaquinone in each of these strains. Based on the above observation Growth at/on:…”
Section: Chemotaxonomic Characterisationmentioning
confidence: 87%
“…The GenBank accession number for the 16S rDNA sequence of strain FCS-11 T is JF896464. fr/k/kocuria.html) and all these species have been isolated from different environmental sources: Kocuria rosea, Kocuria varians and Kocuria kristinae (Stackebrandt et al 1995), Kocuria palustris and Kocuria rhizophila (Kovacs et al 1999), Kocuria polaris (Reddy et al 2003), Kocuria marina (Kim et al 2004), Kocuria carniphila (Tvrzova et al 2005), Kocuria aegyptia (Li et al 2006), Kocuria himachalensis (Mayilraj et al 2006), Kocuria flava and Kocuria turfanensis (Zhou et al 2008), Kocuria gwangalliensis (Seo et al 2009), Kocuria halotolerans (Tang et al 2009), Kocuria koreensis (Park et al 2010b), Kocuria atrinae (Park et al 2010a), Kocuria salsicia (Yun et al 2011) and Kocuria assamensis (Kaur et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…nov. [63], Kocuria atrinae sp. nov. [64], Paenibacillus tyraminigenes sp. nov. [65], Salinicoccus jeotgali sp.…”
Section: Microbial Community Of Jeotgalmentioning
confidence: 99%
“…Kocuria  species ( Kocuria spp) inhabit the normal skin and mucous membrane of human and animals [1]. Kocuria  was also isolated from various environmental and ecological niches [2]. These are usually considered as non-pathogenic bacteria which are rarely associated with human infections.…”
Section: Introductionmentioning
confidence: 99%